Prevalence of neurological malformation in newborns at a tertiary care center in Rajasthan, India - Narayan, Jaiprakash; Narayan, Suchitra; Jain, Anil Kumar; Garg, Pukhraj; Karnawat, Bhag Singh (Indian Journal of Child Health, 2019)
Introduction: Many newborns die every year due to various congenital anomalies and those who survive, suffer from long-term morbidity. To deal with birth defects, a large proportion of health resources and workforce is required. Among the various congenital anomalies, neurological birth defects are the leading type. Objective: The objective of the study was to document the epidemiological features and prevalence of congenital neurological anomalies in rural areas. Materials and Methods: This retrospective study was conducted in the department of pediatric of a medical college of Rajasthan. The study population included live births born in our institution between 1990 and 2018. A register was maintained after delivery to document the particulars of neonates with a congenital birth defect and their mothers. We had taken neonatal record from this register and analyzed the data of the past 28 years, retrospectively. Results: Of 241,848 live births, 6623 cases were identified with a primary diagnosis of one or more congenital anomalies giving a prevalence rate of 274/10,000 live births (95% confidence interval [CI]: 262.2–285.8). Anomalies of the nervous system were the second common defects, accounting for 19.95% of the birth defects just after the heart disease anomalies (21.65%). Neurological anomalies were diagnosed in 1321 neonates. The prevalence of neurological anomalies was 54.62/10,000 live births (95% CI: 49.75–59.49). The most common neurological anomaly was myelomeningocele/meningocele (spina bifida cystic) found in 64.87% of cases followed by Chiari malformation (7.72%), encephalocele (6.89%), microcephaly (6.88%), hydrocephalous (1.43%), and spina bifida occulta (1.43%). Conclusion: Neurological anomalies were among common congenital anomalies and considerable cause of mortality and morbidity. Myelomeningocele/meningocele (spina bifida cystic) was the most common neurological anomaly.